P163 Patient choice: is the local HIV service preferred?. (23rd May 2012) - Andrews, S; Howard, L
Abstract : Aim: To investigate the distance travelled by patient to a specialist HIV clinic in the Home Counties. Methods: Retrospective review of the electronic database of HIV patients attending the clinic from January 2011 to January 2012. Data on gender, ethnicity, sexual orientation, age and residential postcode was collected. The distance to our service was compared to that of the nearest available specialist clinic HIV clinic for each patient. Demographic data were also collected. χ 2 Tests were performed to compare categorical data. Results: 220 patients attended. The median age was 41 years, range 15–74. Our clinic was the closest HIV service for 89 (40%) patients. Of the 131 who selected our service in preference to their local service, 50% travelled up to 10 miles, 15% 11–20 miles, 14% 21–30 miles and 21% more than 30 miles. Interestingly the nearest service for 13 (10%) of these patients was an inner city teaching hospital. There was no significant difference in age, gender or sexual orientation between those who lived locally or travelled further, except for ethnicity. 66% of White British men and women were prepared to travel further for their HIV care compared to 51% for other ethnic groups (p=0.02) (see abstract P163 table 1 ). Conclusions: More than half our HIV patient cohort elected to travel further rather than utilise their local HIV services. The reason for this choice is unclear. However this study highlights the importance of considering patient choice when commissioning, planning and providing HIV services. Further research exploring the reasons for patient preference may aid our understanding of the aspects of HIV care that are particularly valued by our patients.